1989
DOI: 10.3164/jcbn.6.109
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Local Hyperthermia Treatment on Skin SOD Activity in Mice

Abstract: SummaryThe effect of local hyperthermia treatment (43°C, 45 min) on normal mouse skin was studied by examining superoxide dismutase (SOD) activity and histology of the skin. SOD activity of the skin decreased significantly 1, 4, 7, and 14 days after the treatment. The decrease reached a peak 4 days after the treatment and recovered to some extent by 14 days after the treatment. The decrease in SOD activity may be due to consumption of SOD by inflammation as well as to the destruction of SOD by hyperthermia. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1994
1994
2016
2016

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 13 publications
0
1
0
Order By: Relevance
“…In agreement with our results, Arnaud et al 35 reported that a 15-minute heat stress at 42°C did not modify SOD activities of the myocardium in Wistar rats. Yoshioka et al 36 reported unaltered activity of SOD after hyperthermia that could be attributed to degradation of SOD by heat. Induction of catalase in treated tumor observed in our study indicates attenuation of oxidative stress, and indirectly suggests elevation of reactive oxygen species in the tumor after hyperthermia.…”
Section: Discussionmentioning
confidence: 99%
“…In agreement with our results, Arnaud et al 35 reported that a 15-minute heat stress at 42°C did not modify SOD activities of the myocardium in Wistar rats. Yoshioka et al 36 reported unaltered activity of SOD after hyperthermia that could be attributed to degradation of SOD by heat. Induction of catalase in treated tumor observed in our study indicates attenuation of oxidative stress, and indirectly suggests elevation of reactive oxygen species in the tumor after hyperthermia.…”
Section: Discussionmentioning
confidence: 99%